A study of communication apprehension and self concept among undergraduates in UiTM Pahang / Rahimah Abd Wahab, Siti Khalijah Majid and Rohana Awang - Abd Wahab, Rahimah; Majid, Siti Khalijah; Awang, Rohana (2012)
Numerous studies have been done on the subject of communication apprehension (CA) among university students but none has adequately addressed the issue of perception. This study tries to examine the relationship between self concept and communication apprehension among undergraduates. It attempts to find out whether students' perception of themselves and their negative or positive self image have had any effect on their ability to communicate either orally or in writing. The study involves 169 respondents from the Bachelor in Office Management programme in UiTM Pahang. It was discovered that majority of the degree students have low CA and high self-concept. The level of CA in some speaking situations such as public speaking and meetings is still high, and majority admitted to having anxiety when speaking in a formal situation. It is felt that the degree students lack exposure to real life workplace communication. Thus, a few suggestions are given with regards to this aspect, specifically to enable them to hone their communication skills with people outside the university especially business people or professionals. it is hoped that the findings can help lecturers identify better approaches in tackling learners' problem in communicating in the classroom as well as prepare them for future workplace communication events.